Digital Adaptation Strategies for MSMEs in the Vuca Era: A Study of SMEs in Sukabumi City - Maulana, Rizky; Alhidayatullah; Setiadi, Sandi (GoAcademica Research & Publishing, 2025)
This study aims to analyze in depth the influence of digital marketing and product innovation on the competitiveness and sustainability of MSMEs in Sukabumi City in facing the challenges of the VUCA (Volatility, Uncertainty, Complexity, Ambiguity) era. The research method used a mixed method, where a quantitative approach with Structural Equation Modeling-Partial Least Square (SEM-PLS) analysis techniques was reinforced by qualitative interviews to explore the practical perspectives of business actors. The results show that digital marketing plays an important role in expanding market reach, enhancing brand image, and building consumer loyalty as the foundation for business sustainability. Product innovation has also been proven to be significant in creating differentiation, maintaining relevance to dynamic market needs, and increasing added value for consumers. However, competitiveness does not function as a significant mediating variable between digital marketing and product innovation on business sustainability. These findings contribute theoretically by enriching the literature on the dynamic capabilities of MSMEs, while challenging the traditional view that competitiveness is the only major factor in business sustainability. Practically, the results emphasize the importance of consistent innovation, the use of digital technology, and the support of an integrated business ecosystem in maintaining the sustainability of MSMEs amid the uncertainty of the VUCA era.